AN INVESTIGATION INTO EFL PRE-SERVICE TEACHERS’ PERCEPTIONS OF PEER FEEDBACK IMPLEMENTED IN WRITING CLASSES AT THE UNIVERSITY OF DANANG – UNIVERSITY OF FOREIGN LANGUAGE STUDIES (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aims to investigate the implementation of peer feedback in English writing courses at UD – UFLS as well as the perception of third-year and final-year ELTE students of the effectiveness of PF in assisting their writing performance.